STRUCTURAL COMPOSITION OF MODERN GENERAL SECONDARY EDUCATION AND SCHOOL MANAGER ACTIVITIES - Joraeva Nargiza Jamolidinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Today, the changes and developments in every sphere of our society demand modernity from the education system. Especially the development of general secondary education, which is the main link of education, is the demand of today. Based on this, the quality of school education serves as the basis of national security, global stability, long-term development and prosperity. In this article, the structural composition of modern general secondary education and the activities of the school manager, the laws of modern school management, management methods, all structural levels of effective management, the characteristics of modern school activities, the content and essence of the components of modern general secondary education, and the views of scientific researchers on this concept analytical approach.